NEW POSSIBILITIES OF RADIOLOGIC DIAGNOSTICS OF BREAST CANCER - A. B. Abduraimov; S. K. Ternovoy (ABV-press, 2014)
Early breast cancer diagnosis is contemporary and actual problem due to the increase of breast cancer incidence and low detection rate of the disease.Multispiral computed tomography of mammary gland with intravenous contrast agent injection allows resolving diagnostic tasks aris- ing in patients with high density mammary gland tissue, considerable edema, fibrosis, postoperative conditions. It also helps to define localization, extent of disease and tumor growth patterns.High gradient of contrasting in the malignant tissue during venous phase makes it possible to reveal small tumor nodules (less than 1 cm). Implementation of thin slices (less than 1 mm) during multispiral CT of mammary glands allows detecting of micro-calcifications. Possibilities to evaluate changes in retro mammary space, regional lymph nodes and to analyze the osseous and pulmonary tissues con- dition during the same investigation allows correct staging of disease and assessing the degree of disease extension.